Recent Trends in Carbon Nanotubes Based Prostate Cancer Therapy: A Biomedical Hybrid for Diagnosis and Treatment - Murugesan, Raja; Raman, Sureshkumar (Current Drug Delivery, 2022)
At present, treatment methods for cancer are limited, partially due to the solubility, poor cellular distribution of drug molecules and the incapability of drugs to cross the cellular barriers. Carbon Nanotubes (CNTs) generally have excellent physio-chemical properties, which include High-level penetration into the cell membrane, high surface area, and high capacity of drug-loading by circulating modification with biomolecules, projecting them as an appropriate candidate to diagnose and deliver drugs to Prostate Cancer (PCa). Additionally, the chemically modified CNTs possess excellent 'biosensing' properties, thus helping them detect the PCa easily without a fluorescent agent and additionally, targeting the particular site of PCa. In this way, drug delivery can accomplish high efficacy, enhanced permeability with less toxic effects. While CNTs have been mainly engaged in cancer treatment, a few studies are focused on the diagnosis and treatment of PCa. Here, we have meticulously reviewed the current progress of the CNTs-based diagnosis and the targeted drug delivery system for managing and curing PCa.
Keywords: diagnosis